Simple Broadband Quasi-Optical Spatial Multiplexer in Substrate Integrated Technology - Gomez-Tornero, Jose Luis; Martinez-Ros, Alejandro Javier; Mercader-Pellicer, Salvador; Goussetis, George (IEEE transactions on microwave theory and techniques, 2015)
We present a new type of broadband spectral-spatial quasi-optical decomposer for microwave analog signal processing fully implemented in substrate integrated waveguide (SIW) technology. An input SIW is modulated to couple energy to a near-field focused surface wave inside the hosting substrate. Due to its inherent spatially dispersive response, the focal point location varies with frequency. Thus, by placing output SIW ports at the appropriate positions, the focused signal can be extracted for each frequency providing instantaneous spectral decomposition. A design with six output channels from 11 to 16 GHz with 4-dB insertion losses and 1-ns group-delay swing is illustrated. Experiments on a prototype are reported to prove the feasibility of the proposed approach.